Evaluasi Situs Web Menggunakan Website Accessibility Conformance Evaluation Methodology (WCAG-EM) 2.0 pada Situs-Situs E-Commerce di Indonesia - Ahmad Hanafi; Choerun Asnawi (Politeknosains, 2020)
E-Commerce website in Indonesia have grown rapidly. Accessibility test on these kind of website have not been done, this trigger the question, Are disable people capable of using these website to raise their economic. This study is done by using WCAG 2.0 framework to two of the biggest emarketplace website on Indonesia. Bukalapak and Tokopedia. The result those website have shown that there were very low accesibility score between those website.